Anxiety And Existence In Sylvia Plath's The Bell Jar(1966) Novel: An Existentialist Approach - Haryani, Riyan, Dr. Phil. Dewi Chandraningrum, S.Pd. M.Ed, Titis Setyabudi, S.Si (2013)
The object of this study is The Bell Jar novel that is written by Sylvia Plath. This study about how anxiety and existence of the major character are reflected in The Bell Jar novel written by Sylvia Plath published in 1966. These objectives of the study are, firstly to analyze the novel based on structural elements, secondly to analyze the novel based on the structural and the existentialist approach. This study is a qualitative study. The data sources are divided into two, namely primary data source and secondary data source. In collecting data, the writer reads the novel comprehensively and reads some related books to find out theory, data, and information required. For technique of the data analysis, the writer uses descriptive technique. The result of the study comes to the three following conclusions. First, based on structural element in The Bell Jar, it shows that character and characterization, setting, plot, point of view, and theme. Second, based on existentialist theory by Sartre, the writer focuses on analyzing the structure of personality, which consists of the Being, Existence before Essence, Consciousness (Cogito), Freedom to Choose, Anxiety, Transcendence of Ego, and Nothingness. Three, based on the existentialist analysis human have different anxiety and existence, their existence are based on different being, choice, and act. The human's existence is meaningful if he starts his being which has a good action to show his life purpose.